(untitled) (Research, Society and Development, 2022)
Introduction: Parenchymal kidney cancer in adults accounts for 2% to 3% of all malignant neoplasms, affecting 30,000 North Americans annually and killing 12,000 a year. In Brazil, the incidence of this neoplasm varies from 7 to 10 cases per 100,000 inhabitants/year in more industrialized areas, with lower rates in less developed regions. Methodology: The search platform on the following sites: SciELO, Google academic, International Brazilian Journal of Urology, The Journal of Urology, PUBLAB and PUBMED. The descriptors were: “Renal Cell Carcinoma”; “Renal Neoplasms”; “Risk Factors”, “Applications of Epidemiology” and “Smoking”. Outcome and Discussion: Increased incidence of kidney cancer has been reported in most countries over the past three decades, but data are limited for assessing trends in renal cell and renal pelvis cancers separately. With the exception of smoking and the use of phenacetin-containing analgesics, few risk factors are established for cancer of the renal pelvis. Since the late 1960s, phenacetin has become generally unavailable in most industrialized countries and eventually banned from markets. The remainder of this review, therefore, focuses on risk factors for renal cell cancer. Conclusion: In conjunction with the consortium’s efforts to gather detailed exposure data and biological samples from well-designed epidemiological studies, these innovative technologies promise new insights into genetic determinants and how their interaction with the environment can influence the etiology of renal cell câncer.